Kemampuan Laba dan Arus Kas Operasi dalam Memprediksi Laba dan Arus Kas Masa Depan - Lumbantoruan, Frans AP Dromexs; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2018)
This study aims to determine the ability of earnings and operating cash flows in predicting earnings and future cash flows. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange. The samples used by 20 companies with 40 observations. The sampling was done by nonprobability samplingmethod with purposive samplingtechnique. The analysis technique used is multiple linear regression analysis. Based on the result of the analysis, earnings influences in predicting future earnings. Likewise, earnings and operating cash flow have an effect in predicting future cash flows. However, operating cash flow is not influential in predicting future earnings. Keywords: profitability, cash flow, property